PRODUCTIVITY OF PURSE SEINE UNIT AT THE SIBOLGA FISHERIES PORT - Widya Angel Bancin; Arthur Brown; Ronald .M Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT            This research was conducted in July 2019 at the Sibolga Archipelago Fisheries Port. he purpose of this study is to calculate the productivity of purse seine vessels and fishermen, as well as determine the factors that influence fisheries productivity at the Sibolga Archipelago Fishery Port. Productivity of capture and annual purse seine capture units on 10 vessels has increased and decreased each year due to settings, weather and season. Productivity of capture and annual purse seine capture units on 10 vessels has increased and decreased each year due to settings, weather and season. The productivity of fishermen in the purse seine line has increased and decreased 10 units of vessels in the Sibolga Archipelago Fisheries Port because the number of fishermen does not match the weight of the ship. Factors that affect fishing productivity are the weight of the ship (GT) and the number of crew (fishermen). By obtaining the results of multiple regression equations is Y = -18221 + 728X1 – 48,8X2 + 0,00014X3. Keywords: productivity, purse seine fisihing gear, fishierse port Sibolga